Effects of Inflammatory Cytokine Tumor Necrosis Factor-α on Human Mesenchymal Stem Cell Gene Expression: A Mechanism for Liver Regeneration - Maryam Ayatollahi (International Journal of Pediatrics, 2014)
Introduction Insulin-like growth factor I (IGF-I) which is produced in abundance in the normal adult liver, is deeply involved in hepatocyte survival, growth, and differentiation during liver development. IGF-I plays the roles via the receptor (IGF-IR) signaling pathway. IGF-IR unlike IGF-I is expressed strongly in the developing liver, but much more weakly in adults. Objective:  We hypothesized that inflammatory cytokines in liver injury may activate human liver progenitor cells to increase expression of IGF-1R, mediate IGF-1 and its cognate receptor-signaling pathways which contribute to liver regeneration. Methods: To study this, bone marrow-derived mesenchymal stem cells (MSCs) were aspirated from human normal donor after obtaining informed consent. Cells were divided into nine experimental groups and stimulated with inflammatory cytokine tumor necrosis factor-α (TNF-α). Evaluation of differential expression of IGF-1R in TNF-α-treated human MSCs was done by real time polymerase chain reaction. Results: The MSCs were CD11b (CR3), CD45, CD34, CD31 (PCAM-1), CD40, CD80 (B7-1), and HLA-class II negative because antigen expression was less than 5%, while they showed a high expression of CD90, and CD73. The differentiation of osteoblasts, is determined by deposition of a mineralized extracellular matrix in the culture plates that can be detected with Alizarin Red. Adipocytes are easily identified by their morphology and staining with Oil Red.  The real time-PCR data reflected increased expression of IGF-IR in human MSCs upon TNF-α stimulation in a dose response manner. Conclusion: We concluded that ex vivo TNF-α affects IGF-1R expression in human marrow-derived MSCs and might contribute to in vivo-stimulation of liver progenitor cell affected by local inflammatory cytokines due to IGF-1R expression and liver regeneration after injury. It can be a strategy to improve stem cell-effectiveness before in vivo-cell transplantation. Keywords: Adult stem cells, Insulin-like growth factor-I, Gene expression,  Liver regeneration.